`PENGARUH SUHU PENYIMPANAN TERHADAP SIFAT FISIKO KIMIA VARIETAS UMBI DAHLIA - Rapidos, Rotua; Efendi, Raswen; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research was aimed to get the influence storage temperature on physical chemical of red, white and yellow dahlia tubers varieties. This research was conducted experimentally used Completely Randomized Design with four treatments and four replicates on each variety. Data were analyzed by Analysis of variance test followed by Duncan's New Multiple Range Test at level 5%. Treatments of storage temperature in this research were P0 (control), P1 (4ºC), P2 (10ºC) and P3 (26ºC). Results of analysis showed that the storage temperature had a significant effect on water content, weight loss ash , reduce sugar, fiber and inulin content. The best treatment was P1 (4ºC) as for on red dahlia tuber have water content 78.21%, weight loss 0.93%, reduce sugar 4.86%, fiber 6.06%, ash 1.09% and inulin 57.79%, on yellow dahlia tuber have water content 78.50%, weight loss 0.90%, reduce sugar 5.20%, fiber 6.68%, ash 1.57% and inulin 66.06%, and on white dahlia tuber, have water content 79.57%, weight loss of 0.97%, reduce sugar 5.75%, fiber 7.64%, ash 2.09% and inulin 78.37%. Keywords: Dahlia tubers, varieties, storage temperature.